La gastro-entérite chez les nourrissent et jeune enfants (0 à 5 ans) - Reguieg yssaad, cherine (My University, 2020)
Gastroenteritis is one of the main causes of mortality and morbidity throughout the world, especially in developing countries. Malnutrition is a factor contributing to the worsening of diarrheal diseases in children 0 to 5 years old. The incidence of diarrheal diseases is observed throughout the year with a high peak in the dry season. The prevalence of astroviruses in the world varies from 2 to 16% (Hamkar et al, 2010) and the parasitic one still remains high in most of the poor countries. The aim of our study is to establish the prevalence of astroviral and parasitic infections in children with diarrhea under 5 years old in the hospital Cheguevara Mostaganerm. In our entire sample, malnutrition affects 59.7% of children with a high prevalence in children under 24 months. Rotaviruses have a prevalence of 15/66 (22.73%) and 1/66 (1.52%) of A denovirus and that of Parasites 8 out of 66 (12.12%) cases of infections by Protozoa. Among the isolated parasites(Giardia lambia and Trichomonas intestinalis) versus 4 cases (6.06%) of Helminths (Strongyloïdes stercoralis and Hymenolepis nana). The high prevalence of rotaviruses is observed in children under 24 months and parasitic in those over 24 months. Breastfeeding is a protective factor against episodes of diarrhea. Season and age are believed to be the causes of fluctuations in the incidence of diarrhea in children under 5 years old. Knowledge of all the aetiologies involved in diarrhea is necessary for effective control of childhood gastroenteritis.
Keywords: Gastroenteritis; rotavirus; Parasites; Malnutrition.